(untitled) (Texas Journal of Medical Science, 2026)
Social media has become an integral part of adolescents’ daily lives, significantly influencing their social, emotional, and cognitive development. Platforms such as Instagram, Facebook, TikTok, Snapchat, and other networking sites provide opportunities for communication, education, entertainment, and self-expression. However, excessive use of social media may also expose teenagers to numerous risks. This article examines both the positive and negative effects of social media on adolescents, with particular attention to mental health challenges, cyberbullying, addiction, academic performance, privacy concerns, and sleep disruption. The paper further discusses the role of parents, educators, and policymakers in promoting safe and responsible social media use. Finally, strategies for minimizing the harmful effects of social media are presented. A balanced approach is necessary to maximize the benefits of social media while protecting teenagers from its potential dangers.